Chavismo : Genealogia de una pasion politica - Rodríguez, Indhira Libertad; Bracamonte, Leonardo (CLACSO, 2017)
Co-published by CELARG and CIM. Whoever wants to understand the extraordinary experience of the national-popular governments that toured the Latin American world starting in the first decade of the 21st century should concentrate their comprehensive efforts on an examination of the type of mobilization that was undertaken during the previous stages, the profile radically plural of the mobilized subjects and the diverse demands deployed during the years of the struggles against the macroeconomic adjustment plans. This book is the result of a passionate political debate, but at the same time that cannot be postponed, which gave an account of the differences of a movement whose radically heterogeneous composition is a constitutive consequence of its own history.